THE EFFECT OF CORONA VIRUS ON THE GLOBAL CLIMATE - Sri Rahayu Pudjiastuti; Sopian ,; Nestiyanto Hadi (UNIVERSITAS PAKUAN, 2020)
The Covid-19 pandemic has worried the international community. Countries in the world have banned their citizens from leaving their homes, to avoid transmission of the corona virus. Based on this policy, indirectly it has an effect on air pollution. The earth is clean again with an appeal to just stay at home. The corona virus has changed people's views on climate change. Although on the other hand the corona virus has had a negative impact on global economic conditions. This study aims to provide an overview and analysis of the effect of corona on the global climate. This research method uses a descriptive analysis method supported by secondary data and literature studies. Climate can affect the stability of covid-19, the corona virus can be stable at temperatures of 1oC to 10oC with a humidity of 40% to 50%. Indonesia, which is located on the equator with an average temperature of 27 to 30oC and humidity of 70% to 95%, is an area that is not ideal for the Covid-19 epidemic. However, the facts show that cases of Covid-19 have spread in Indonesia. This means that the population mobility factor has more influence on the development of Covid-19 in Indonesia. Thus it can be concluded that air temperature and humidity can be the dominant factors for the spread of the corona-19 virus. Thus the spread of the Covid-19 epidemic can be controlled by climate and weather factors, human demographics and mobility, as well as social interactions, and also determines public health interventions.